Mortality risk factors among critically ill children with MIS-C in PICUs: A multicenter study - Şık, Güntülü; İnamlık, Ayşegül; Akçay, Nihal; Kesici, Selman; Aygün, Fatih; Kendirli, Tanıl; Atay, Gürkan; Kılıç, Ahmet Osman (Springer Nature, 2023)
BackgroundThis study evaluated of clinical characteristics, outcomes, and mortality risk factors of a severe multisystem inflammatory syndrome in children admitted to a the pediatric intensive care unit.MethodsA retrospective multicenter cohort study was conducted between March 2020 and April 2021 at 41 PICUs in Turkey. The study population comprised 322 children diagnosed with multisystem inflammatory syndrome.ResultsThe organ systems most commonly involved were the cardiovascular and hematological systems. Intravenous immunoglobulin was used in 294 (91.3%) patients and corticosteroids in 266 (82.6%). Seventy-five (23.3%) children received therapeutic plasma exchange treatment. Patients with a longer duration of the PICU stay had more frequent respiratory, hematological, or renal involvement, and also had higher D-dimer, CK-MB, and procalcitonin levels. A total of 16 patients died, with mortality higher in patients with renal, respiratory, or neurological involvement, with severe cardiac impairment or shock. The non-surviving group also had higher leukocyte counts, lactate and ferritin levels, and a need for mechanical ventilation.ConclusionsIn cases of MIS-C, high levels of D-dimer and CK-MB are associated with a longer duration of PICU stay. Non-survival correlates with elevated leukocyte counts and lactate and ferritin levels. We were unable to show any positive effect of therapeutic plasma exchange therapy on mortality.ImpactMIS-C is a life-threatening condition.Patients need to be followed up in the intensive care unit.Early detection of factors associated with mortality can improve outcomes.Determining the factors associated with mortality and length of stay will help clinicians in patient management.High D-dimer and CK-MB levels were associated with longer PICU stay, and higher leukocyte counts, ferritin and lactate levels, and mechanical ventilation were associated with mortality in MIS-C patients.We were unable to show any positive effect of therapeutic plasma exchange therapy on mortality.
Keywords: PICUs; Mortality Risk Factors; MIS-C; Among Critically